Biblical Foundations For Manhood And Womanhood - Grudem, Wayne (Wheaton, Ill. Crossway Books, 2002)
For years a debate has raged over how to define true masculinity and true femininity. While there is agreement that men and women share equally in the privilege of being made in God's image, some views of manhood and womanhood blur God-given gender dist
Keywords: Women -- Biblical teaching. Men -- Biblical teaching. Man-woman relationships -- Biblical teaching